Comparative retrospective study on the modalities of biopsying peripheral neuroblastic tumors: a report from the Italian Pediatric Surgical Oncology Group (GICOP). Issue 5 (20th October 2016) - Avanzini, Stefano; Faticato, Maria Grazia; Crocoli, Alessandro; Virgone, Calogero; Viglio, Camilla; Severi, Elisa; Fagnani, Anna Maria; Cecchetto, Giovanni; Riccipetitoni, Giovanna; Noccioli, Bruno; Leva, Ernesto; Sementa, Angela Rita; et al.
Abstract: Background: Peripheral neuroblastic tumors are the most common extracranial solid neoplasms in children. Early and adequate tissue sampling may speed up the diagnostic process and ensure a prompt start of optimal treatment whenever needed. Different biopsy techniques have been described. The purpose of this multi‐center study is to evaluate the accuracy and safety of the various examined techniques and to determine whether a preferential procedure exists. Methods: All children who underwent a biopsy, from January 2010 to December 2014, as a result of being diagnosed with a peripheral neuroblastic tumor, were retrospectively reviewed. Data collected included patients' demographics, clinical presentation, intraoperative technical details, postoperative parameters, complications, and histology reports. The Mann–Whitney U and Fisher's exact tests were used for statistical analysis. Results: The cohort included 100 patients, 32 of whom underwent an incisional biopsy (performed through open or minimally invasive access) (Group A), and the remaining 68 underwent multiple needle‐core biopsies (either imaging‐guided or laparoscopy/thoracoscopy‐assisted) (Group B). Comparing the two groups revealed that Group A patients had a higher rate of complications, a greater need for postoperative analgesia, and required red blood cell transfusion more often. Overall adequacy rate was 94%, without significant differences between the two groups (100% vs. 91.2% for Group A and Group B, respectively, P = 0.0933). Conclusions: Both incision and needle‐core biopsying methods provided sub‐optimal to optimal sampling adequacy rates in children affected by peripheral neuroblastic tumors. However, the former method was associated with a higher risk of both intraoperative and postoperative complications compared with the latter.